2017
DOI: 10.1212/wnl.0000000000003558
|View full text |Cite
|
Sign up to set email alerts
|

Olfaction and risk of dementia in a biracial cohort of older adults

Abstract: Objective: Prior studies indicate that olfactory function may be an early marker for cognitive impairment, but the body of evidence has been largely restricted to white populations. Methods:We studied 2,428 community-dwelling black and white older adults (baseline age 70-79 years) without dementia enrolled in the Health, Aging, and Body Composition (Health ABC) study. Olfaction was measured as odor identification (OI) with the 12-item Cross Cultural Smell Identification Test in year 3. We defined incident deme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
105
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 44 publications
9
105
0
Order By: Relevance
“…Effect modification by race was examined in one study, which stratified its cohort into black and white. The magnitude of association between olfactory impairment and risk of dementia was significant among both groups; however, the association was weaker among black compared with white participants …”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Effect modification by race was examined in one study, which stratified its cohort into black and white. The magnitude of association between olfactory impairment and risk of dementia was significant among both groups; however, the association was weaker among black compared with white participants …”
Section: Resultsmentioning
confidence: 82%
“…Interestingly, the presence of apolipoprotein E (APOE)‐e4 allele was found to modify the effect of olfactory impairment and cognitive decline in one study, wherein the association was strongest among those who were anosmic with at least one allele (OR 4.93, 95% CI, 1.63–14.91), especially among women (OR 9.71, 95% CI 1.34–70.44). However, a different study found no interaction between APOE genotype and olfactory impairment on incident dementia.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…An additional strength that gives this study its broad implications is that olfaction is predictive of dementia even in cognitively intact older adults, extending prior work with high-risk populations and smaller, more-homogenous samples. [1][2][3][4][5][6][7] Why would olfactory dysfunction precede the development of dementia? One potential explanation is that the neuropathology underlying dementia, such as AD (amyloid-b plaques and paired helical filament tau tangles), may begin earlier in the olfactory system than the cortex.…”
Section: Discussionmentioning
confidence: 99%